The Human Ecology of Disasters in Ethiopia: The Quest for Participatory Disaster Management and Sustainable Livelihood Improvement of Pastoral Communities - Ogato, Gemechu Shale (American Journal of Human Ecology, 2013)
<!--[if gte mso 9]> <![endif]--> A desk review was conducted during the period 2012 on the quest for participatory disaster management and sustainable livelihood improvement of pastoral communities of Ethiopia from human ecological perspective. Pastoral communities in Ethiopia have issues related to access to and quality of pasture and water, animal health care, domestic and international markets and indigenous, domestic and international strategies for relief and recovery assistance. The general objective of this paper is to evaluate the disaster management system in Ethiopia from sustainable disaster management system perspective. The paper adapts human ecological research approach. Comprehensive literature review on disasters and disasters management was conducted in the course of writing this paper. The findings of the study reveal that disasters like droughts, floods, conflict, insect infestations, and earthquakes occur in Ethiopia. In other words, Ethiopia is vulnerable to disasters caused by drought, earthquake, flood, war and conflict, human and livestock diseases, pests, wildfire and landslide, amongst others. Reversing the history of pastoral communities in Ethiopia needs strong commitment of the government of Ethiopia to design and implement appropriate and sustainable pastoral community development policy and strategy. In other words, there is a need for Ethiopia to have comprehensive and participatory disaster management system which can address both response to disasters and disaster risk management. Moreover, the financial and technical support of international agencies might enhance the endeavor of the country to mitigate disasters and reduce disasters risk. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->